Thiamphenicol in the treatment of cholera in children - Haroen Noerasid; Eko Sujanto; Ismoedijanto Ismoedijanto; Djoko Soejono; I. G. G. Djelantik; Surata Surata (Indonesian Pediatric Society, 1981)
A study has been performed to measure the efficacy of thiamphenicol by comparing it with tetracycline as a standard drug. Eighty bacteriologically confirmed cholera patients were included in this study.Among them, 41 patients were treated with thiamphenicol while the other39 with tetracycline.Stool volume, duration of diarrhea and duration of hospitalization were higher in the thiamphenicol group. And the volume of intravenous and oral fluid therapy were less in the tetracycline group.Positive bacteriologic examinations of the second samples (taken on the second day of hospitalisation) of the thiamphenicol grollp were 41.46% as compared with 17.94% of the tetracycline group. But almost all o the third samples of both groups were negative.Clinical success rate of thiamphellicol was 95.12% and tetracycline was 100%. Thiamphenicol appeared to be effective against cholera in children.",